The management model of the company Nutricbal S.C. and the support by technological resources and enterprise resource planning systems Odoo-Open ERP - Revelo Chacón, Eduardo Daniel (SATHIRI, 2023)
The objective of this research focuses on determining the management model for the company Nutricbal S.A. through the configuration of an enterprise resource planning system (ERP) open source, to improve the efficiency of the processes in such a way that, to achieve this objective, the current situation of the company was evaluated based on performance indicators (KPIs) of time, costs and resources to measure the efficiency of the processes and in the same way the methodological framework of COBIT 5 was applied. 0, which measures the use of information technologies (IT) at the supply chain level, establishing a maturity level of 1. Subsequently, the modules of purchasing, inventory, warehousing, manufacturing, customer relationship management (CRM), sales, billing, website and e-commerce were configured in Odoo, which is an open source system that is able to adapt to any type of company, be it small, medium or large. Finally, based on the simulation of the management model, the KPIs were measured, achieving an optimization in the efficiency of logistics processes (supply, storage, production and distribution) in terms of time, costs and resources, placing the management model in a maturity level 5 due to its automation and digital transformation of the business.